Analisis A Debt-For-Nature Swap Sebagai Alternatif Mengurangi Utang Indonesia Kepada Luar Negeri - Siahaan, Hinsa (Journal the Winners: Economics, Business, Management, and Information System Journal, 2006)
Given the size of Indonesiaâ€™s foreign debt and the rate of forest destruction,Â â€œa debt-for-nature swapsâ€ seems an obvious solution. In these schemes, a portion of aÂ nationâ€™s public debt is bought by a third party at substantial discount. The debt then iscancelled. In return, the country promise to protect severall million hectares of forests.Â This research focused on dicussion of the possibility of the Government of The RepublicÂ of Indonesia to reduce its foreign debt by using a debt-for-nature swap.Â